120k views
1 vote
Integrate 1 - x / x(x2 + 1) d x by partial fractions.

User Rrk
by
4.7k points

1 Answer

2 votes

Answer:


log x-(log(x^(2)+1) )/(2)-tan^(-1) x

Explanation:

step 1:- by using partial fractions


[tex](1-x)/(x(x^(2)+1) ) =(A(x^(2)+1)+(Bx+C)(x )/(x(x^(2)+1) )......(1)

step 2:-

solving on both sides


1-x=A(x^(2) +1)+(Bx+C)x......(2)

substitute x =0 value in equation (2)

1=A(1)+0

A=1

comparing x^2 co-efficient on both sides (in equation 2)

0 = A+B

0 = 1+B

B=-1

comparing x co-efficient on both sides (in equation 2)

-1 = C

step 3:-

substitute A,B,C values in equation (1)

now


\\\int\limits^ {} \, (1-x)/(x(x^(2)+1) ) d x </p><p>=\int\limits^ {} (1)/(x) d x +\int\limits^ {} (-x)/(x^(2)+1 ) &nbsp;d x -\int\limits (1)/(x^(2)+1 ) &nbsp;d x

by using integration formulas

i) by using
\int\limits (1)/(x) &nbsp; d x =log x+c........(a)</p><p>\\\int\limits (f^(1)(x) )/(f(x)) d x= log(f(x)+c\\.....(b)


\int\limits tan^(-1)x &nbsp;dx =(1)/(1+x^(2) ) +C.....(c)

step 4:-

by using above integration formulas (a,b,and c)

we get answer is


log x-(log(x^(2)+1) )/(2)-tan^(-1) x

User Abdul Rizwan
by
4.7k points